2010
DOI: 10.1111/j.1365-2672.2009.04528.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization and heterologous expression of the firstPenicillium echinulatumcellulase gene

Abstract: Aims:  Penicillium echinulatum is effective for bioconversion processes. However, nothing is known about the molecular biology of its cellulolytic system. We describe for the first time the isolation, cloning and expression of a P. echinulatum cellulase cDNA (Pe‐egl1) encoding a putative endoglucanase. Methods and Results:  Pe‐egl1 cDNA was identified from random sequencing of a P. echinulatum cDNA library. The deduced EGL1 protein possibly belongs to the glycosyl hydrolase family 5A, with 387 amino acid resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 50 publications
3
18
0
1
Order By: Relevance
“…However, the activity of Spr Cel8A increased in the presence of Co 2+ , Mn 2+ , Li 1+ and Na 1+ (1 and 5 mM), and other metallic ions such as Cu 2+ , Ni 2+ and Fe 2+ at 1 mM, and Ca 2+ 5 mM. This suggests that this endoglucanase manifests a conformational stability, because the enzyme retained its activity even in the absence of metallic ions (Welfle et al 1995; Rubini et al 2010). An increase of 139.5 % in the activity of an endo-1,4-β-glucanase from B. subtilis was observed in the presence of Co 2+ (Au and Chan 1987); whereas Spr CelA from S. proteamaculans increased by 108 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the activity of Spr Cel8A increased in the presence of Co 2+ , Mn 2+ , Li 1+ and Na 1+ (1 and 5 mM), and other metallic ions such as Cu 2+ , Ni 2+ and Fe 2+ at 1 mM, and Ca 2+ 5 mM. This suggests that this endoglucanase manifests a conformational stability, because the enzyme retained its activity even in the absence of metallic ions (Welfle et al 1995; Rubini et al 2010). An increase of 139.5 % in the activity of an endo-1,4-β-glucanase from B. subtilis was observed in the presence of Co 2+ (Au and Chan 1987); whereas Spr CelA from S. proteamaculans increased by 108 %.…”
Section: Discussionmentioning
confidence: 99%
“…4b). Enzyme inhibition by metallic cations usually suggests the presence of at least one sulfhydryl group in the active site, usually a cysteine amino acid (Rubini et al 2010). This group oxidation by the cations destabilizes the conformational folding of the enzyme (Rouvinen et al 1990) or leads to the formation of disulfide bonds at an irregular position of the protein (Ohmiya et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several endo-b-1,4-glucanases from Penicillium pinophilum KMJ601 [19], P. purpurogenum [22], and P. echinulatum [32] have been reported, but all of them only have the ability to hydrolyze the b-(1 ? 4) glycosidic bonds of glucan.…”
mentioning
confidence: 99%
“…Compared to other groups of extremophilic microorganisms, such as thermophiles and alkaliphiles, halophiles have not often been utilized in biotechnological processes, even though researchers recently predicted that halophiles may be used to break down biomass material and form biofuel products (25). The ThCel5A we cloned from T. halotolerans YIM 90462 T was tolerant to most ions, especially to Pb 2þ and Ag þ , which are well-known to be toxic to enzymes by oxidizing their sulfhydryl groups (26). In contrast, Ca 2þ and Mn 2þ stimulated the activity of ThCel5A, which was most likely due to the ability of Ca 2þ to stabilize an enzyme conformation with a higher affinity for the substrate, while Mn 2þ hyper-stabilized the catalytic core (26,27).…”
Section: Discussionmentioning
confidence: 98%
“…The ThCel5A we cloned from T. halotolerans YIM 90462 T was tolerant to most ions, especially to Pb 2þ and Ag þ , which are well-known to be toxic to enzymes by oxidizing their sulfhydryl groups (26). In contrast, Ca 2þ and Mn 2þ stimulated the activity of ThCel5A, which was most likely due to the ability of Ca 2þ to stabilize an enzyme conformation with a higher affinity for the substrate, while Mn 2þ hyper-stabilized the catalytic core (26,27). However, Endo et al found that the activity of Egl-252, an alkaline GH5 endoglucanase from an alkaliphilic Bacillus isolate, was more stable in the absence of CaCl 2 (28).…”
Section: Discussionmentioning
confidence: 99%